A Samsung production system-based approach to improve manufacturing process management in Vietnamese firms - Nguyen, Minh Dat (Zielona Góra: Faculty of Economics and Management Press)
Today, more and more Vietnamese firms consider continuous improvement as the best way to increase their manufacturing capability. This paper aims to illustrate the effectiveness of manufacturing processes management from the Samsung production system (SPS) approach when it was implemented to improve capability of existing production process in Vietnamese firms.
Keywords: Vietnamese firms; Manufacturing process; continuous improvement; Samsung Production System